Mechanisms of tissue degeneration mediated by periostin in spinal degenerative diseases and their implications for pathology and diagnosis: a review - Yoshihara, Tomohito; Morimoto, Tadatsugu; Hirata, Hirohito; Murayama, Masatoshi; Nonaka, Toshihiro; Tsukamoto, Masatsugu; Toda, Yu; Kobayashi, Takaomi; Izuhara, Kenji; Mawatari, Masaaki (Frontiers in Medicine, 2023)
Periostin (POSTN) serves a dual role as both a matricellular protein and an extracellular matrix (ECM) protein and is widely expressed in various tissues and cells. As an ECM protein, POSTN binds to integrin receptors, transduces signals to cells, enabling cell activation. POSTN has been linked with various diseases, including atopic dermatitis, asthma, and the progression of multiple cancers. Recently, its association with orthopedic diseases, such as osteoporosis, osteoarthritis resulting from cartilage destruction, degenerative diseases of the intervertebral disks, and ligament degenerative diseases, has also become apparent. Furthermore, POSTN has been shown to be a This is a provisional file, not the final typeset article valuable biomarker for understanding the pathophysiology of orthopedic diseases. In addition to serum POSTN, synovial fluid POSTN in joints has been reported to be useful as a biomarker. Risk factors for spinal degenerative diseases include aging, mechanical stress, trauma, genetic predisposition, obesity, and metabolic syndrome, but the cause of spinal degenerative diseases (SDDs) remains unclear. Studies on the pathophysiological effects of POSTN may significantly contribute toward the diagnosis and treatment of spinal degenerative diseases. Therefore, in this review, we aim to examine the mechanisms of tissue degeneration caused by mechanical and inflammatory stresses in the bones, cartilage, intervertebral disks, and ligaments, which are crucial components of the spine, with a focus on POSTN.